Antecedents of The Product-Website Appeal and its Impact Toward Usage Intention - Christopher Noviandi Tupang; Ferdi Antonio (Institute of Computer Science (IOCS), 2021)
House is one of the basic needs of humans which is hard to get because of it’s relatively high price nowadays especially according to millenial segment. Therefore, bank provides an installment method to make it easier for buying a house immediately by using Kredit Pemilikian Rumah (KPR) product where one of the banks that provides this product is Bank Central Asia (BCA). Along with era transformation in which most services has begun to make a transition to digital channels, BCA provides an alternative method for applying KPR by utilizing digital channel namely by submitting online through it’s KPR website. The purpose of this study is to examine the impact of product-website appeal’s antecedents toward usage intention. This test was conducted using the PLS-SEM method on 216 respondent obtained using purposive sampling distributed online. The results show that the strongest positive relationship is product appeal to website appeal and the strongest influence on usage intention is trust. This research model has moderate predictive accuracy and medium predictive relevance to the dependent variable usage intention. There is managerial insight from the findings of this study as well as recommendations for further research.